COMPARISON BETWEEN ACUTE TOXICITY AND CHEMICAL ANALYSIS OF NATURAL GAS DRILLING EFFLUENT SAMPLES USING PENAEUS MONODON - Yayah Rodiana; Daam Settachan; Thundorn Saneanukul; Jerry Diamond (Jurnal Ecolab, 2011)
The regulation of point source discharges usually based on specific chemicals which describe thresholds below which no adverse impact on the receiving water. The limitation of this technique includes the fact that it does not take into account interactions among toxicants (e.g. additivity, synergism, antagonism). Therefore, toxicity testing is recommended as integrated approach for identifying toxic pollutants to complement chemical-specific analysis by assessing the sum toxicity of all components in the mixture. The objective of this research was the assessment of Penaeus monodon (PM) as an indicator species for toxicity testing through comparisons between results from 48-h LC50 and chemical analysis of the natural gas drilling effluent. Chemical analysis of effluent samples was performed in order to determine concentrations of BTEX (benzene, toluene, ethyl benzene, xylene) and heavy metals (Cr, Ni, Cu, As, Pb, Cd). Average 48-h LC50’s for PM was 2,94 % for effluent and 0.68 g/l for KCl. Comparison between acute toxicity and chemical analysis showed a significant correlation between toluene concentrations and 48-h LC50 in PM (p<0.05). No significant correlation was found between the detectable heavy metal concentrations and acute toxicity data in PM. Results suggest that the lack of correlation between toxicity and almost all chemical parameters indicates that toxicity testing is much more useful for monitoring toxicity of effluents than chemical analysis. Additional studies are needed to identify alternative toxicity endpoints as sensitive indicators of impacts on the environments